進路選択の変化と進路不決断 : 中学男子生徒3年間の縦断調査の分散分析 - 清水, 和秋; 坂柳, 恒夫 (進路指導研究, 1991)
The purpose of the present study was to investigate whether changes in career choice status were accompanied by changes in the educational and vocational indecision dimensions. The factorial scales of educational and vocational indecision dimensions developed by Shimizu (1989a, 1990) were administered to 106 junior high school male students at three times, one year apart. Depending on their responses to the career choices after graduating senior high school at three grades, subjects were placed in: consistent university type (university-university-university [N=10]); convergent university type (university/college/vocation/undecided-university/college/vocation/undecided-university [N=24]); unstable university type (university/college/undecided-university/undecided-college/undecided [N=8]); unstable type (college/ undecided-college/ undecided-college/undecided [N=14]); consistent undecided type (undecided-undecided-undecided [N=14]); consistent vocation type (vocation-vocation-vocation [N=5]); convergent vocation type (university/vocation/undecided-college/vocation/undecided-vocation [N=22]); unstable vocation type (vocation/undecided-vocation/undecided-college/undecided [N=9]). Many significant differences by the repeated ANOVA tests on the educational and vocational indecision scales were found at career choice types except the consistent university type.